Multiaxial Fatigue Behaviour Of Heat Treated 6061 Aluminium Alloy - Marno, Marini (2011)
This study is devoted to investigate the response of solid and thin-walled tubular specimen made of as-received and heat treated into T4 and T6 6061 aluminium alloy subjected to axial (tension-tension), torsional and axial torsional low cycle fatigue. 6061 aluminium alloys have been widely used as a candidate material in aerospace, automobile, aircraft and structural application because of their superior mechanical properties such as high strength to weight ratio and good ductility. In this investigation, the response and behaviour of this alloy to the cyclic loading were studied using cyclic stress response and cyclic stress strain curve shows that this alloy exhibits cyclic hardening. The geometry of the hysteresis loops is also being analyzed in order to evaluate the softening and hardening effect. The effects of heat treatment on the fatigue life and behaviour where T6 condition depict higher fatigue life are discussed. The differences in fatigue behaviours and cyclic deformation between solid and round specimens where a stress gradient exist, and thin-walled tubular specimens where a uniform stress state is assumed are also discussed. Fatigue life of the specimens were recorded and presented in the S-N curve and shows that heat treated T6 alloy exhibits higher fatigue life and fatigue strength compared to the as-received and T4 alloy regardless the type of cyclic loading applied. Cracks initiate on the maximum shear plane and then start to propagate depending on the type of cyclic loading that were applied to the specimens. Through fractographic analysis, shallow striations and various sizes of dimples and voids are observed during the crack propagation while the final overload region exhibits dimples rupture.